Application of Problem Based Learning Model Assisted by Android Learning Media to Increase High School Students' HOTS on Redox Reaction Material - Hardiansyah, Teddy; Pohan, Lisa Ariyanti; Hasanah, Uswatun (Universitas Lampung, 2024)
Abstract: Application of Problem Based Learning Model Assisted by Android Learning Media to Increase High School Students' HOTS on Redox Reaction Material. This study aims to describe the application of the problem-based learning model assisted by Android learning media to increase students' higher-order thinking skills (HOTS) on redox reaction material. The method used in this study is the quasi-experimental design method, with the type of research design used being a non-equivalent control group design. The research sample selected is X MIA 2 as a control class and X MIA 3 as an experimental class. The research will be conducted at SMA Negeri 2, Tanjung Morawa, in August 2023. Data collection techniques use HOTS-laden essay tests and observation sheets on learning implementation. Data analysis techniques used to measure student success and improvement of HOTS use independent sample t-tests and N-gains, while for the implementation of learning and student response, they use a Likert scale. The results of the study were obtained where there was a significant influence in the application of the problem-based learning model assisted by android learning media in increasing students' HOTS on redox reaction material with an independent test of t-test samples at α= 0.05 obtained sig. 2-tailed by 0.000 from the post-test value of the control class and experiment, the N-gain value of 0.55 in the medium category. In addition, the implementation of learning gets an average percentage of 88.19%. Thus, it can be concluded that the problem-based learning (PBL) model assisted by Android learning media can help train and improve students' higher-order thinking Skills (HOTS).Keywords: Problem-Based Learning, Android Learning Media, Higher Order Thinking Skill, Redox Reactions.DOI: 10.23960/jppk.v13.i1.2024.11